Effect of hornbeam sawdust size on the mechanical properties of polyethylene composites - KARTAL, İLYAS (ICE PUBLISHING, 2020)
Composite materials obtained with natural and sustainable fibers can be used successfully in many areas on their own. In recent years, high-strength fibers such as hemp, sisal, linen, jute, wood sawdust and bamboo are more preferred in composite materials. In this study, the effect of the hornbeam sawdust size on the mechanical properties of polyethylene was investigated. For this purpose, different sizes of hornbeam sawdust were added to polyethylene. Hornbeam sawdust was added to the polyethylene matrix in four different weight ratios (5, 10, 15 and 20%) by way of the extrusion method. Test samples were prepared out of those mixtures by injection-molding. Tensile, Izod impact and hardness tests were performed on the samples. The elastic modulus increased with increasing hornbeam sawdust content. However, elongation at break and Izod impact strength values decreased. Modulus of elasticity, tensile strength, elongation at break and Izod impact strength values decreased with increasing hornbeam sawdust size. The morphology of composite samples was examined by scanning electron microscopy. The results show that the hornbeam sawdust can be used as a filler in polymer-based composites.
Keywords: composite materials; mechanical properties; morphology; GREEN COMPOSITES; FIBER; MATRIX